Pengembangan Assesmen Autentik Berbasis Proyek pada Mata Kuliah Biologi Terapan Melalui Model Pembelajaran Kooperatif Tipe Group Investigation - Nur, Sri Mukminati; Rasjid, Yusniar (Biology Teaching and Learning, 2018)
Abstract. This study aims (i) to find out the stages of project-based device development in applied biology courses through cooperative learning models type group investigation; (ii) To find out the quality of project appraisal devices in applied biology courses through cooperative learning models group investigation in terms of validity and reliability in terms of validity, reliability, practicality, level of difficulty and power difference. This research is the development of devices using formative research type development research models. In the study using one class as the research subject and one small group trial class for the sixth-semester students in the applied biology semester even the 2017/2018 academic year. The results of the study show (i) Development of authentic assessment tools using the Plomp model which consists of 5 phases namely 1) the initial phase; 2) design phase; 3) construction phase; 4) the test and evaluation phase; 5) the implementation phase is produced by the appraisal device which: (ii) is valid as evidenced by the existence of a correlation coefficient from the cognitive assessment tool, psychomotor assessment, and affective assessment greater than 0.35 and a significance value smaller than the 5% significance level. Reliable, based on the results of empirical reliability test using Cronbach Alpha formula obtained the value of the correlation coefficient of cognitive assessment devices, psychomotor assessment, and overall effective assessment greater than 0.76. Objective, objectivity test analysis using ANAVA formula for cognitive appraisal, psychomotor assessment, and overall affective assessment obtained the results of the significance of the observer greater than the 5% significance level which means that no variation in the assessment carried out by the three observers. Practically, an analysis of the practicality of the authentic assessment device has a validity of 4.05 with a very valid category. Whereas in the data from observers' observations, the value of implementation (TL) was 3.64 with the category mostly implemented.Keywords: project-based authentic assessment, cooperative learning model type group investigation.Â